2016
DOI: 10.1021/acs.iecr.6b01095
|View full text |Cite
|
Sign up to set email alerts
|

Potassium-Salt-Catalyzed Tar Reduction during Pyrolysis Oil Gasification

Abstract: The gasification of pinewood pyrolysis oil with potassium hydroxide dissolved was investigated, using a potassium salt loaded char as catalyst, to screen if this would result in a lower tar yield in the product stream. Experiments were performed at 700 °C, after which the product stream was thoroughly condensed and the gas stream was analyzed. The results show a significant tar reduction for a fixed potassium-loaded char bed at a gas hourly space velocity (G C1 HSV) of 237 h −1 . If the G C1 HSV is reduced, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…36 Therefore, the pronounced effect of impregnation on tar yields between T = 900 and 1000 °C is most likely due to the promoted secondary reactions. The second pathway, i.e., K 2 CO 3 salt as the heterogeneous catalyst, 22,23 seems to be relevant because the char particles from K-impregnated sawdust were permeable and alkali salts were deposited on the surface of char particles (see Figure 8). The direct interaction between alkali metal elements and tar molecules in the gas phase (pathway 3) was also apparent in our study.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…36 Therefore, the pronounced effect of impregnation on tar yields between T = 900 and 1000 °C is most likely due to the promoted secondary reactions. The second pathway, i.e., K 2 CO 3 salt as the heterogeneous catalyst, 22,23 seems to be relevant because the char particles from K-impregnated sawdust were permeable and alkali salts were deposited on the surface of char particles (see Figure 8). The direct interaction between alkali metal elements and tar molecules in the gas phase (pathway 3) was also apparent in our study.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Unlike the extensive literature about char gasification, literature is limited for the catalytic activity of alkali metal salts on tar and soot formation. Most studies have investigated either the shift of products from liquid to gas/char during devolatilization or catalytic tar reforming over the beds of alkali salts or alkali-loaded char. , Only few studies have investigated the effect of alkali metal salts in the gas phase or suspended in a gas flow, which is the condition relevant to the entrained-flow gasifiers. Simonsson et al investigated the formation of soot in an ethylene/air flame with the seeding of various metal chlorides and showed that KCl reduced the soot volume fraction and particle sizes .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to catalytic steam reforming of tar, biochar catalysts were also employed for reforming other bioderived resources such as bio-oil or bio-gas. Thus, for the gasification of bio-oil at 700 • C, Postma et al, developed a potassium salt loaded biochar catalyst [69]. Both the K dissolved in the pyrolysis oil feed and the K-loaded biochar catalysts were found to enhance the gas yield (ca.…”
Section: Reforming and Gasification Reactionsmentioning
confidence: 99%
“…Alkali metal salts seem to be the earliest catalysts to be examined for gasification [29]. Alkali elements were studied to catalyze gasification of char and biomass, and they were proved to reduce the formation of tar and soot [30,31]. The employment of catalysts is preferred for entrained-flow gasifiers, which will be discussed later [32].…”
Section: Catalystsmentioning
confidence: 99%